Foundations for a disequilibrium theory of the business cycle : qualitative analysis and quantitative assessment - Chiarella, Carl (Cambridge University Press, 2005)
Finally, topical issues in monetary policy are studied in small macromodels as well as for the KMG model by incorporating an estimated Taylor-type interest rate reaction function. The stability features of this enhanced model are also compared to those of the original KMG model."--Jacket
Keywords: Business cycles -- Econometric models.; Equilibrium (Economics); Cycles économiques -- Modèles économétriques.; POLITICAL SCIENCE -- Economic Conditions.; BUSINESS & ECONOMICS -- Economics -- Macroeconomics.; Business cycles -- Econometric models; Electronic books.